Liminal, littoral, labile: The moving edge of the sea - Stocker, Laura (Gallery of the John Curtin Gallery at Curtin University, 2011)
The exhibition will be a mixed-media collection of around ten student works each focused on the possible social, cultural, ecological and economic impacts of climate change on our coastline. Students will be asked to contribute a response that represents in some way the scientific forecasts about climate change and the coast. Humans have pushed out towards the sea from the land and ‘reclaimed’ the seabed, built groynes and marinas, dredged harbours and even proposed new islands. There are long and short-term natural events and cycles that mean the coastline is a dynamic edge. Human activity is now interacting with these forces so that climate change will affect the coastline and our life on it. The coast is an ecological system that is fragile and valuable. The coast is a favoured residential place by many. The sea and coast is also a site for social and cultural interaction for many Australians. The beach is a place where coastal dwellers pass through many rites of passage and significant life experiences: learning to swim as children, first sexual encounters and beach parties as adolescents, honey-moons as newly-weds, summer holidays as families and retirement pleasures. Finally, the sea is a site for industry, labour and commerce. All of these values are potentially under threat from climate change impacts such as storm surges and rising sea levels, as forecast by scientists. The purpose of this exhibition is for student artists to reflect on the liminal, littoral and labile nature of the edge of the sea, and on its vulnerabilities to climate change.Student artists will be approached about contributing to the exhibition and those interested will be invited to attend an interactive workshop presented by Curtin researchers on climate change and the coast. Up to ten works will be commissioned for exhibition. There is also a research component to this exhibition. Viewers and artists will be surveyed about the works with a view to understanding the relationships among artistic and scientific representations of coastal change. The results will inform the CSIRO Coastal Collaboration Cluster, whose goal is to find innovative ways to make climate change research about the coast more accessible (Stocker et al, 2010). (Associate Professor Laura Stocker at CUSP is the Deputy Leader of this research Cluster). Curtin University has an excellent art school and there are many researchers working on the issues of climate change and the coast. The exhibition is a way of bringing these groups of people together in a collaboration to share their insights. The technical details will be for the student artists to decide. Works can be paintings, sculptures or digital productions.